Intervention wiht laser in lingual frenulum with anterior and fibrous insertion. Case report - Rolando - Altamirano, Gabriela (2020)
The lingual frenulum is a mucous membrane. This structure is important for the mobility of the tongue, if the frenulum has a short insertion, it can difficult the movements of the tongue and affect the eruption of the lower incisors. Case report: This work reports the case of a girl, 4 years old, who comes with her tutor to the Dental Center of the Scientific University of the South telling: "I want to have her tongue checked". After performing exams, ankyloglossia was diagnosed. The girl presented a lingual frenulum with fibrous anterior insertion, a heart-shaped tongue and struggle in articulating certain phonemes. Consultations with Speech and Pediatrics were sent. After the signature of the informed Consent by the person in charge and the responseof the consultations, surgical disinsertion was proposed as a treatment plan: Frenectomy. The surgery was performed successfully. The patient was referred to speech therapy to work the phonemes with difficulty. Conclusion: The frenectomy allowed to recover the functions of the tongue like language and manage toexecute movement properly.